Peningkatan Tata Kelola Koperasi Simpan Pinjam Pembiayaan Syari’ah BUEKA Walidah Mulia - Rahmawati, Alni; Wahyuningsih, Rr. Sri Handari (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
The Sharia Funding, Savings, and Loans Cooperative (KSPPS) BUEKA Walidah Mulia (BWM) is a national sharia secondary cooperative established by the Aisyiyah Central Executive Labor Economic Council. Each provincial secondary cooperative has three primary sharia cooperatives. KSPPS BWM is the parent of national cooperatives as a strategic driver in reviving and assisting secondary/primary cooperatives. The problem faced by KSPPS BWM is that the capacity of human resources (managers) in organizational governance is not standardized. The purpose of empowering KSPPS BWM is to increase the capacity of managers in cooperative governance according to Cooperative Governance Standards. The applied methods in the program were socialization, education, focus group discussions (FGD), mentoring, monitoring, and evaluation. The results of the empowerment show that the capacity of KSPPS BWM cooperative managers in terms of knowledge and skills of standard cooperative management increases. The implication of the service program is that the performance of KSPPS BWM cooperative management increases and is able to carry out the control function to better managed secondary/primary cooperatives.Â